Diversity of Arbuscular Mycorrhizal Fungi Associated with Six Rice Cultivars in Italian Agricultural Ecosystem Managed with Alternate Wetting and Drying - Veronica Volpe; Franco Magurno; Paola Bonfante; Stefano Ghignone; Erica Lumini (Rice Science, 2023)
Alternate wetting and drying (AWD) system, in which water has been reduced by approximately 35% with an increased occurrence of beneficial arbuscular mycorrhizal (AM) symbiosis and no negative impact on rice yield, was proposed to utilize water and nutrients more sustainable. In this study, we selected six rice cultivars (Centauro, Loto, Selenio, Vialone nano, JSendra and Puntal) grown under AWD conditions, and investigated their responsiveness to AM colonization and how they select diverse AM taxa. In order to investigate root-associated AM fungus communities, molecular cloning-Sanger sequencing on small subunit rDNA data were obtained from five out of the six rice cultivars and compared with Next Generation Sequencing (NGS) data, which were previously obtained in Vialone nano. The results showed that all the cultivars were responsive to AM colonization with the development of AM symbiotic structures, even if with differences in the colonization and arbuscule abundance in the root systems. We identified 16 virtual taxa (VT) in the soil compartment and 7 VT in the root apparatus. We emphasized that the NGS analysis gives additional value to the results thanks to a more in-depth reading of the less represented AM fungus taxa.